Response of pipeline Nepalese maize hybrids to different doses of chemical fertilizers under varying plant densities - Adhikari, Jagat Bandhu; K.C., Govind; Regmi, Dhurba (Journal of Agriculture and Natural Resources, 2020)
Low plant population and inadequate fertilizer application are constraints for maize production among farmers in Nepal. In order to identify the integrated effects of plant density and fertilizer dose for production of hybrid maize, series of on station experiments were carried out at Rampur, Chitwan, Nepal using strip plot design with three replications during winter seasons in two consecutive years 2016/17 and 2017/18. Two promising Nepalese hybrids namely RML-95/RML-96 and RML-86/RML-96 were taken as vertical factor whereas five densities viz. 55,555 ha-1(D1), 66,666 ha-1 (D2), 77,519 ha-1 (D3), 87,719 ha-1 (D4) and 98,039 ha-1 (D5) in combination with two doses of NPK fertilizers i.e. recommended and rational as horizontal factor. Recommended dose of NPK for maize was 120:60:40 kg ha-1 and the rational doses for above mentioned densities were calculated based on bench mark of fertilizer recommendation for 53,333 plants ha-1. Derived rational doses of NPK for D1, D2, D3, D4 and D5 were 125:63:42, 150:75:50, 174:87:58, 197:99:66, 221:110:74 kg ha-1 respectively. Genotypic variation of two tested hybrids for growth, yield attributes and grain yield were found statistically similar. However, planting the hybrids in various densities and fertilizer doses significantly influenced grain yield ranging from 5.63 to 7.91 t ha-1. Significantly higher grain yield (7.91 t ha-1) and benefit cost ratio (2.21) were observed when plant population was maintained at 77,519 ha-1 with fertilizer dose 174:87:58 NPK kg ha-1. Applying fertilizer as rational dose enhanced the yield up to the density of 77519 plants ha-1 then the yield gradually declined as the density increased. Whereas recommended dose of fertilizer with increasing plant density from 55,555 to 87,719 ha-1 had statistically similar yield and declined more at 98039 ha-1. The present recommended dose of fertilizer application is inadequate for higher plant density to increase the grain yield of hybrid maize